Association of XRCC1 and XPD polymorphism with risk of prostate cancer in Bangladesh population - Ahmed, Nafisa (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.